The Male Face of Caregiving: A Scoping Review of Men Caring for a Person With Dementia. (September 2014) - Robinson, Carole A.; Bottorff, Joan L.; Pesut, Barbara; Oliffe, John L.; Tomlinson, Jamie
The purpose of this scoping review was to examine the empirical evidence published since 2007 on men as family caregivers of persons with dementia. Searches were conducted on Academic Search Complete, Ageline, CINAHL, Embase, Medline, PsychINFO, Social Work Abstracts, and Web of Science using database-specific controlled (i.e., MeSH terms) vocabulary related to dementia, men, and caregiving. Studies published in English between 2007 and 2012 that provided evidence of the experiences of male family caregivers of persons with dementia were included in the review. A total of 30 articles were selected for inclusion. Studies were grouped into three major themes for review: men's experiences of caregiving, relational factors, and outcomes of caregiving. The reviewed studies build on and support previous findings related to stress, burden, accessing services, and the importance of relational factors to men's caregiving experiences. However, there is a need for a framework that explains these findings in relation to masculinities. Such a framework would provide the necessary unifying context for a more powerful explanatory account. Furthermore, there appears to be the potential for great benefit in fully linking men's caregiver research to men's health issues as a means to articulate strategies to sustain the health and well-being of men caregivers. This seems especially relevant in light of the closing gender gap in life expectancy, which will ultimately see many men providing direct care to their partners.